Polyphase deformation of the Youjiang fold-and-thrust belt during the Mesozoic: Implications for the tectonic transition of the South China block - Hu, Jia-Xiu; Xiao, Chang-Hao; Wei, Chang-Shan; Shen, Yu-Ke; Chen, Zheng-Le; Zhang, Yu; Zhang, Da (Frontiers in Earth Science, 2023)
Abstract: The South China Block (SCB) experienced the tectonic transition from Paleo-Tethys to Paleo-Pacific during the Mesozoic. But the transition process is debated. The Youjiang Basin in southwestern SCB is located in a junction affected by the Paleo-Tethyan and Paleo-Pacific domains, developing structural features of the above two tectonic domains and thus keeping the record of structure evolvement integrally. Therefore, the Youjiang Basin is an intriguing window into the Mesozoic evolution in the southwestern SCB. The Youjiang fold-and-thrust belt (YFTB) is a boundary that separated the northern thin-skinned structure and the southern thick-skinned structure. Hence, the YFTB is advantageous to better understand the Mesozoic tectonic evolution and tectonic transition process of the SCB. In this study, we conducted structural analysis at the central part of the YFTB and discuss the tectonic transition of the SCB. Four phases of deformation are identified in the YFTB during the Mesozoic. The first phase deformation (D1) is characterized by NW-SE trending thrust faults, synclinore and conjugated joints resulting from NE-SW shortening which are related to the collision between the SCB and Indochina Block. The second phase deformation (D2) is manifested as the pre-existing NW-SE striking thrust faults transformed as normal faults and Late Triassic mafic magmatism. Our structural observation, combined with previous geochronology data of mafic dykes, implies the study area occurred in the Late-Triassic post–orogenic extension. The third phase deformation (D3), accompanied with the westward subduction of the Paleo-Pacific oceanic plate, is represented by a series of conjugated joints and NE–SW trending faults, formed by NW-SE compression. As a result of continuous subduction of the Paleo-Pacific plate and its subsequent slab rollback, the fourth phase deformation (D4) is featured with normal faults, magmatic–hydrothermal activity and regional mineralization, which is associated with the nearly E–W extension setting. Our study results indicate that, in the Early Mesozoic, the Youjiang Basin was dominated by the Paleo-Tethyan domain and then transferred into the Paleo-Pacific domain. The apparent quiescence between the Triassic and Early-Middle magmatic rocks implies that transition process of the SCB manifested in the YFTB is more likely initiated in the Early Jurassic.